Security and Privacy Challenges, Solutions, and Open Issues in Smart Metering: A Review - Win, Lae Lae; Tonyali, Samet (Institute of Electrical and Electronics Engineers Inc., 2021)
The traditional power grid becomes ‘smart’ when it is combined with the communication and information technology. Along with smart grid, the traditional meter is replaced with smart meter. Smart meters play an important role in energy consumption reporting and, thereby, billing. Besides smart meters, the smart grid communication network is composed of heterogeneous devices that are communicating through public networks. Therefore, smart metering communications are susceptible to cyber-attacks and privacy breaches which are still under debating. This paper gives a brief overview of smart grid, smart metering, and the communication networks. Then, the privacy and security requirements of the smart grid network are derived. The various kind of cyber-attacks are discussed, after that, the different schemes and approaches that have been proposed in previous papers are reviewed. Lastly, the open issues on security and privacy of smart grid metering communications are highlighted. © 2022 Elsevier B.V., All rights reserved.
Keywords: Cybersecurity; Privacy; Smart Grid; Smart Metering; Computer Crime; Crime; Cyber Attacks; Electric Measuring Instruments; Electric Power Transmission Networks; Energy Utilization; Network Security; Smart Meters; Communications Networks; Cyber Security; Energy-Consumption; Heterogeneous Devices; Power Grids; Privacy; Security and Privacy; Smart Grid; Smart Grid Communications; Smart Metering; Smart Power Grids